FOXO1 Content Is Reduced in Cystic Fibrosis and Increases with IGF-I Treatment - Smerieri, Arianna (Int J Mol Sci, 2014)
Cystic fibrosis-related diabetes is to date the most frequent complication in cystic fibrosis (CF). The mechanisms underlying this condition are not well understood, and a possible role of insulin resistance is debated. We investigated insulin signal transduction in CF. Total insulin receptor, IRS1, p85 PI3K, and AKT contents were substantially normal in CF cells (CFBE41o-), whereas winged helix forkhead (FOX)O1 contents were reduced both in baseline conditions and after insulin stimulation. In addition, CF cells showed increased ERK1/2, and reduced β2 arrestin contents. No significant change in SOCS2 was observed. By using a CFTR inhibitor and siRNA, changes in FOXO1 were related to CFTR loss of function. In a CF-affected mouse model, FOXO1 content was reduced in the muscle while no significant difference was observed in liver and adipose tissue compared with wild-type. Insulin-like growth factor 1 (IGF-I) increased FOXO1 content in vitro and in vivo in muscle and adipose tissue. In conclusion; we present the first description of reduced FOXO1 content in CF, which is compatible with reduced gluconeogenesis and increased adipogenesis, both features of insulin insensitivity. IGF-I treatment was effective in increasing FOXO1, thereby suggesting that it could be considered as a potential treatment in CF patients possibly to prevent and treat cystic fibrosis-related diabetes.